2017
DOI: 10.1016/j.jid.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Blue Rubber Bleb Nevus (BRBN) Syndrome Is Caused by Somatic TEK (TIE2) Mutations

Abstract: Blue rubber bleb nevus syndrome (Bean syndrome) is a rare, severe disorder of unknown cause, characterized by numerous cutaneous and internal venous malformations; gastrointestinal lesions are pathognomonic. We discovered somatic mutations in TEK, the gene encoding TIE2, in 15 of 17 individuals with blue rubber bleb nevus syndrome. Somatic mutations were also identified in five of six individuals with sporadically occurring multifocal venous malformations. In contrast to common unifocal venous malformation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 33 publications
1
142
0
3
Order By: Relevance
“…Both TEK mutations found in the BRBN case were present in cis . As all mutated reads contained both mutations, the same variant allele frequency was suggested . In contrast to the literature, our TEK mutated cases were histologically more heterogeneous showing also combined lesions with a venous, capillary, and/or a lympathic component.…”
Section: Discussionsupporting
confidence: 40%
“…Both TEK mutations found in the BRBN case were present in cis . As all mutated reads contained both mutations, the same variant allele frequency was suggested . In contrast to the literature, our TEK mutated cases were histologically more heterogeneous showing also combined lesions with a venous, capillary, and/or a lympathic component.…”
Section: Discussionsupporting
confidence: 40%
“…BRBNS is a rare sporadic disorder characterized by multiple multifocal venous malformations primarily involving the skin and gastro­intestinal tract. Additionally, somatic mutations in TEK encoding TIE2 were discovered in individuals with BRBNS and determined as the cause of BRBNS [1]. …”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the TIE2 receptor and the PIK3CA signal transducer participate in the same VM signalling pathway, opening new possibilities for evidence-based molecular therapies against VMs [29,31,32,150]. Recent genetic analysis have revealed that allelic TIE2 double mutations are enriched in blue rubber bleb nevous syndrome (BRBN), characterized by multiple VM lesions [151]. ECs expressing recurrent BRBN TIE2 mutation showed increased colony forming capacity in vitro assays that may contribute to the clinically distinct multifocal VM phenotype in BRBN patients [151].…”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%
“…Recent genetic analysis have revealed that allelic TIE2 double mutations are enriched in blue rubber bleb nevous syndrome (BRBN), characterized by multiple VM lesions [151]. ECs expressing recurrent BRBN TIE2 mutation showed increased colony forming capacity in vitro assays that may contribute to the clinically distinct multifocal VM phenotype in BRBN patients [151]. …”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%